STUDY KOMPARASI IMPLEMENTASI SISTEM PEMERINTAHAN PRESIDENSIAL ANTARA NEGARA AMERIKA SERIKAT DAN NEGARA INDONESIA - Toto Andri Puspito; Desta Adinda Rahmadhani (Siyasah Jurnal Hukum Tatanegara, 2022)
After the stipulation of the 1945 Constitution of the Republic of Indonesia in the 4th Amendment, the Indonesian state has declared itself to be consistent in implementing the presidential system of government as the basis for the implementation of its government. The presidential system of government or also known as the congressional system is a system of government in a country in the form of a republic in which executive power is elected through general elections and is separated from legislative power. With the complexity of this system, not many countries that implement it fail to pass the test of democratic stability. It can be stated that only the United States of America is capable of becoming the best practice of implementing a successful, effective and efficient presidential system. Therefore, many other countries use the United States as a role model in building an effective and efficient form of presidentialism system as has been done by Indonesia.